2021
DOI: 10.1080/10872981.2021.1911019
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of an interactive, competency-based pilot pediatric telemedicine curriculum

Abstract: During the height of the COVID-19 pandemic, telemedicine visits surged to increase access and maintain continuity of care, while reducing transmission of disease. However, few curricula exist for training residents on how to care for patients via telemedicine, especially in pediatrics. We aimed to create and evaluate an interactive, competency-based pilot curriculum, to meet the urgent need to train residents in telemedicine. The curriculum was developed in 2020 and includes a didactic, cased-based discussions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 6 publications
(6 reference statements)
0
18
0
Order By: Relevance
“…Education and training in telemedicine is important for improving pediatric providers’ acceptance of and comfort with virtual visits. 17 Telemedicine-specific training may also improve the quality of the visits and increase the experience of the encounters for providers, patients, and families. 3 In addition to training focused on delivering care over video, site-specific training around telemedicine workflows and processes is necessary for ensuring comprehensive and compliant documentation.…”
Section: Introductionmentioning
confidence: 99%
“…Education and training in telemedicine is important for improving pediatric providers’ acceptance of and comfort with virtual visits. 17 Telemedicine-specific training may also improve the quality of the visits and increase the experience of the encounters for providers, patients, and families. 3 In addition to training focused on delivering care over video, site-specific training around telemedicine workflows and processes is necessary for ensuring comprehensive and compliant documentation.…”
Section: Introductionmentioning
confidence: 99%
“…The checklist we present in Table 3 is a compilation of multiple institutions’ checklists, originating from a single institution that studied its use in evaluating residents pre/post telemedicine training 15 …”
Section: Utilising Telemedicine For Feedback and Evaluationmentioning
confidence: 99%
“…Direct observation by attendees was also developed for evaluation purposes. 24 There was a significant increase in residents’ self-reported efficacy in performing key components of telemedicine visits. Another study demonstrated that undergraduate medical students taught using DH technologies were more familiar with them in their later clinical practice and more able to use such technologies in their career compared to peers who did not receive DH-based lessons during their training.…”
Section: Introductionmentioning
confidence: 96%